Institutional Innovation of Integrated Cropping Calendar Information System to Support Climate Change Adaptation for National Food Security - Runtunuwu, Eleonora; syahbuddin, haris; Ramadhani, Fadhlullah; Setyorini, Diah; Sari, Kharmila; Apriyana, Yayan; Susanti, Erni; Haryono, Haryono (Pengembangan Inovasi Pertanian, 2013)
Government of Indonesia has set the rice surplus target of 10 million tons in 2014. This program requires integrated and comprehensive efforts of all stakeholders in central and local levels. The policy was set forth in form of Permentan No. 45/2011 and then implemented by the Director General of Indonesian Agency for Agricultural Research and Development (IAARD) through a decree No. 178.1/Kpts/OT.160/I/7/2012 about For- mation of Integrated Cropping Calendar and Climate Change Task Force in each Assessment Institute for Agricultural Technology (AIAT) for whole Indonesia. Additionally, IAARD has developed an Integrated Cropping Calendar Information System as a reference for policy makers in planning food crop management. The information system contains the next planting season estimation at sub-district level, which includes the initial time of planting, disaster-prone areas (flood, drought, and pests/diseases), as well as technology recommendation (varieties, seed, and fertilizer). In order to make an operational standard for AIAT Task Force, the Technical Guideline of Integrated Cropping Calendar and Climate Change is imperative. This article contains the summary of the technical guideline for AIAT Task Force in support of Permentan No. 45/2011 and climate change adaptation for food security. An implication of implementation of the AIAT Task Force is an important part in improving the content of Integrated Cropping Calendar Information System that fits the needs of farmers and extension workers in the field in order to achieve the rice surplus target.Â Â  Â